2018
DOI: 10.1177/1043659617753042
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Aspects of End-of-Life Care Planning for African Americans: An Integrative Review of Literature

Abstract: Advance directive completion rates among the general population are low. Studies report even lower completion rates among African Americans are affected by demographic variables, cultural distinctives related to patient autonomy, mistrust of the health care system, low health literacy, strong spiritual beliefs, desire for aggressive interventions, importance of family-communal decision making, and presence of comorbidities. An integrative review was conducted to synthesize nursing knowledge regarding cultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 33 publications
1
22
1
Order By: Relevance
“…Finally, prior studies found a positive relationship between educational attainment and documented completion of EOL ACP wishes (Lovell & Yates, 2014; Rao et al, 2014; Waite et al, 2013). However, this study’s informants had much higher than average levels of education (67% with baccalaureate degree or higher and 24% with doctoral degrees), yet the percentage of informants with documented EOL ACP wishes was low at only 19% of the sample, within the range of 17% to 24% for all AAs in the United States as reported by Collins et al (2018).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Finally, prior studies found a positive relationship between educational attainment and documented completion of EOL ACP wishes (Lovell & Yates, 2014; Rao et al, 2014; Waite et al, 2013). However, this study’s informants had much higher than average levels of education (67% with baccalaureate degree or higher and 24% with doctoral degrees), yet the percentage of informants with documented EOL ACP wishes was low at only 19% of the sample, within the range of 17% to 24% for all AAs in the United States as reported by Collins et al (2018).…”
Section: Discussionmentioning
confidence: 54%
“…A comprehensive integrative review of the literature revealed multiple cultural care beliefs and characteristics, and a historical perspective of EOL planning of AAs that negatively affect utilization of EOL ACP (Collins et al, 2018) including (a) moderators to personal autonomy including familial and communal decision making, (b) mistrust of the health care system, (c) low health literacy and level of education, (d) importance of religion and belief that life and death are in God’s hands, and (e) desire for aggressive life-sustaining treatments at EOL. However, culture-bound meanings, expressions, and traditions related to EOL ACP among AAs have not been sufficiently studied to identify how nursing and other providers can promote culturally congruent care within the parameters of these beliefs and practices.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In fact, the extant literature highlights variation in medical decision-making preferences among African Americans at the individual level. While many prefer shared EOL decision making and value interconnectedness, 38,109 there is a patient segment that desires selfindependence and wants control of personal health care. 110 Effective tailoring designed to increase AD uptake among African Americans would require identifying the patient's self-construal orientation and developing value-congruent health communications, 111 such as promotional messaging that emphasizes family and relationships or autonomy and self-reliance.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Understanding and respecting diverse racial and ethnic beliefs are essential in EOL care, and encouraging open communication between significant others, family members, friends, and health care providers are essential factors to consider in facilitating a positive dying experience. 31 The purpose of this study was to examine predictors of EOL discussions with significant others, family members, and friends among minority older women aged 50 years and older living with HIV infection. The Social Ecological Model (SEM) guided this study.…”
Section: Introductionmentioning
confidence: 99%